Critical analysis on the UAE Courts’ reaction upon accession to the New York Convention - de Moura, Kath Zagatti Itabaiana (2015)
Despite the UAE having acceded to the New York Convention on 13 June 2006, the positive trend towards the application of its provisions by the Courts has started only in 2011. The current Courts’ jurisprudence, however, is still far from settled as conflicting decisions concerning recognition and enforcement of foreign arbitral awards are being passed by the Courts. Aiming at understanding the Courts’ rationale behind the negative approach towards the New York Convention, twelve Courts’ rulings were thoroughly analyzed. A critical review of the analysis made leads to the conclusion that it is uncertain whether the Courts will apply the New York Convention or the local procedural rules when evaluating a request for enforcement of a foreign arbitral award as the jurisprudence in this respect is evenly divided. It shall nonetheless be noted that the Courts’ negative approach towards the New York Convention might conflict with the provisions of the local rules. On the other hand, a greater compliance of the New York Convention by the Courts can be expected in view of the UAE commitment to become an arbitration-friendly State internationally recognized and the expectation of a new UAE arbitration law based on the UNCITRAL Model Law.